Pengaruh Variasi Radius Lingkaran Singgung Dan Radius Lingkaran Dasar Cam (Nok) Simetris Terhadap Karakteristik Kinematik Gerak Roller Follower - Sutikno, Endi; Sulistyo, Erwin; Anindito, Ariyo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
The study looked at the kinematic analysis of mechanism design cam - follower roller symmetrical with simulations. After designing the geometry of the observed variable cam is cam base circle radius, radius circle tangent, the other constant. With mathematical equations to model the radial displacement, radial velocity, acceleration and jerk radial follower, then made subsequent mathematical tabulations of results generated graph of displacement, velocity, acceleration and jerk of the cam angle swivel. The result is the kinematics characteristic, its maximum on the radius of the circle tangent to the largest and smallest radius circle.Keywords: cam, follower, roller, base circle, the circle tangent, radial displacement, acceleration, jerk.